A Bahasa Indonesia-English translation analysis of Negeri Lima Menara and The Land of Five Towers - Hermawan, Hermawan; Tanjung, Sufriati (Department of Applied Linguistics, Graduate School of Universitas Negeri Yogyakarta, 2018)
The objectives of this research were to describe the types of translation methods, to describe the types of translation procedures, to describe the changes in terms of added and reduced information, and to describe the types of cultural features found in The Land of Five Towers, compared to that of the original novel, Negeri Lima Menara. This research was a qualitative research. This qualitative research applied content analysis to analyse the data. The results of the research were as follows. (1) There were two translation methods found in this research, Semantic Method and Communicative Method. Semantic Method was proven to be the more dominant. (2) There were five translation procedures found: transposition, modulation, adaptation, contextual equivalence, and noted equivalence. Yet, the most prominent procedure applied was transposition. (3) Added information was made on: cultural expressions, names of places, and predicate of the sentences. (4) Reduced information was made on: names of Islamic scholars, arabic expressions, Indonesian expressions, etc. (5) There were five kinds of cultural features found, they were: ecology; material culture or artefacts; social culture; organisations, customs, activities, procedures, and concepts; and gestures and habits.